Differences in treatment response between migraine with aura and migraine without aura: lessons from clinical practice and RCTs - Hansen, Jakob Møller; Charles, Andrew (Journal of headache and pain, 2019)
Migraine is a major public health problem afflicting approximately 10% of the general population and is a leading cause of disability worldwide, yet our understanding of the basis mechanisms of migraine remains incomplete. About a third of migraine patients have attacks with aura, consisting of transient neurological symptoms that precede or accompany headache, or occur without headache. For patients, aura symptoms are alarming and may be transiently disabling. For clinicians and scientists, aura represents an intriguing neurophysiological event that may provide important insight into basic mechanisms of migraine. Several observations point toward important differences between migraine with and without aura. Compared with migraine without aura, migraine with aura has different heritability, greater association with different conditions including stroke, different alterations of brain structure and function as revealed by imaging studies. A number of studies also indicate that migraine with aura may respond differently to acute and preventive therapies as compared to migraine without aura. The purpose of this review is to provide an overview of these differences in treatment responses, and to discuss the possibility of different therapeutic strategies for migraine with vs. without aura.